Pengaruh Kualitas Produk dan Harga terhadap Kepuasan Konsumen Yang Berdampak pada Loyalitas Pelanggan Pemakai Paket Data Internet Indosat Ooredoo (Studi Pada Mahasiswa Prodi Manajemen S-1 Universitas Pamulang) - Aris Ariyanto; Ivantan Ivantan; Purwanti Purwanti (Universitas Batanghari Jambi, 2022)
This study aims to determine the partial or simultaneous effect of product quality and price on consumer satisfaction and customer loyalty of Indosat Ooredoo internet data packages. the research method is associative with a quantitative approach. The population in this study were Indosat Ooredoo internet data package customers at Pamulang University students, with a sample of 128 respondents. data collection techniques by means of a questionnaire. The data analysis technique used instrument test, classical assumption test, path test, coefficient of determination, t-test and F-count test. The results showed (1) partially product quality had a positive and significant effect on consumer satisfaction, as evidenced by the value of t-count > t-table or (17.355 > 1.97897); (2) partially the price has a positive and significant effect on consumer satisfaction, as evidenced by the value of t-count > t-table or (13.971 > 1.97897); (3) partially product quality has a positive and significant effect on customer loyalty, as evidenced by the value of t-count > t-table or (16.459 > 1.97897); (4) partially the price has a positive and significant effect on loyalty as evidenced by the value of t-count > t-table or (11.314 > 1.97897); (5) partially customer satisfaction has a positive and significant effect on customer loyalty as evidenced by the value of t-count > t-table or (14.678 > 1.97897); (6) simultaneously product quality and price have a positive and significant effect on consumer satisfaction, as evidenced by the F-count > F-table or (199.981 > 3.92); (7) simultaneously product quality and price have a positive and significant effect on customer loyalty, as evidenced by the F-count > F-table or (149.418 > 3.92); (8) simultaneously product quality, price and customer satisfaction have a positive and significant effect on customer loyalty as evidenced by the F-count > F-table or (109.744 > 3.07); (9) indirectly through customer satisfaction, product quality on customer loyalty has no significant effect; and (10) indirectly through customer satisfaction, price on customer quality has no significant effect.